Feasibility and Participant Experiences of a Written Emotional Disclosure Intervention for Parental Caregivers of People with Psychosis. (29th July 2015) - Jones, Christina J.; Hayward, Mark; Brown, Abigail; Clark, Elizabeth; Bird, Daniel; Harwood, Gina; Scott, Crystyn; Hillemann, Angela; Smith, Helen E.
Abstract: Caregivers are at increased risk of poor health but often cannot engage with health care because of practical constraints. Writing therapies such as written emotional disclosure (WED) might represent an accessible therapy for this population. This study aimed to determine whether WED is a suitable therapy for caregivers of people with psychosis. Data were collected from a feasibility trial comparing WED with a neutral writing task. Twenty four participants completed writing tasks; the content was analysed using the Linguistic Inquiry Word Count (LIWC) programme. Twenty one participants provided feedback about the writing task, and data were analysed using Burnard's thematic content analysis. WED was feasible to implement in caregivers of people with psychosis. All participants ascribed benefit to writing tasks, the majority describing a cathartic effect, enjoying time to oneself or distraction from caregiving. Quantitative comparison indicated differences in emotional content between intervention and control writing. However, qualitative analysis showed that control participants found it challenging to write neutrally, the majority citing the care‐recipient in their writing. Community‐based WED is a feasible therapy for caregivers of people with psychosis. The need for refinement of the control writing task for use in caregivers is discussed. Copyright © 2015 John Wiley & Sons, Ltd.